KRAS mutational status of endoscopic biopsies matches resection specimens. Issue 7 (29th March 2012) - Yang, Qing-Hua; Schmidt, Jason; Soucy, Genvieve; Odze, Robert; Dejesa-Jamanila, Liza; Arnold, Keely; Kuslich, Christine; Lash, Richard
Abstract : Aims: This study was performed to determine systematically whether KRAS mutational analysis in biopsy tissue is a reliable indicator of KRAS status in subsequent corresponding resection specimens. Methods: 30 colorectal cancer (CRC) patients with biopsy and corresponding subsequent surgical resection specimens were studied. KRAS mutational analysis was performed on each biopsy sample as well as two separate samples from each resection specimen by PCR and Sanger sequencing. Results: Overall, KRAS mutations were identified in 12/30 (40%) of the tumours. There was 100% correlation between biopsy and resection specimens regarding the presence or absence of KRAS mutations. In fact, the same point mutation was identified in both biopsy and corresponding resection specimens in 12/12 (100%) cases. In addition, in two cases, there were two different point mutations detected within the same biopsy specimen. Conclusion: This study shows perfect correlation between KRAS mutation status in biopsy and resection specimens from an individual patient, and suggests that biopsy material is adequate for KRAS mutational analysis in CRC patients.